Atypical antipsychotic prescribing patterns amongst Child and Adolescent Mental Health Services clinicians in a defined National Health Service Trust. (1st January 2016) - Rao, Pradeep; Zepf, Florian Daniel; Chakrabarti, Indranil; Sigalas, Paul
Abstract : Background: In the last decade, the prescription of atypical antipsychotics in minors, by all specialists, has increased. The use has been both licensed and 'off-label', with the aim of targeting different symptoms and clinical conditions. However, most research around safety and efficacy of these pharmacological agents has been conducted in adults and with repeated calls for such research in minors in vain. Objectives: This survey aims to describe current prescribing practices in a 'real-world' scenario and to compare the results with existing research to evaluate lessons learnt. Methods: The survey consisted of a semi-structured questionnaire that aimed to evaluate the current practices of Child and Adolescent Mental Health Services (CAMHS) prescribers. A total of 31 questionnaires sent out yielded 24 completed returns (77.41%). A literature search yielded articles that described prescribing trends over the last decade. The results from the survey were compared with the existing literature. Results: The commonest indication for using atypical antipsychotics in minors was psychosis (75%). Other indications included reduced behavioural control (50%), tic disorders (37.5%), ADHD and anxiety disorders. Atypical antipsychotics were the commonest first-line medications for managing behavioural control with Risperidone (54%) being the most preferred agent. Second-line medications included Quetiapine (7%) and Olanzapine (15%). Doses were lower for managing behavioural control, and atypical antipsychotics were trialled for up to 8 weeks, and with duration of treatment extending up to 9 months. When such medications were used for non-psychotic presentations, most common target symptoms were aggression (85%), agitation (54%) and anxiety (54%). Most prescribers reported peer/expert opinion and their own clinical experience as evidence base for their use and clinical practice. Conclusions: In the investigated sample, atypical antipsychotics continue to be used as first-line medications for psychotic and non-psychotic psychiatric presentations in minors, despite an absence of clear evidence comparable to the adult literature, and also despite repeated calls for in-depth research in this particular population. Although the present survey was conducted amongst psychiatrists, this has implications for all prescribers in children and adolescents, regardless of their specialty.